Cascade synthesis of indolizines and pyrrolo[1, 2-a]pyrazines from 2-formyl-1-propargylpyrroles. Issue 2 (14th December 2021) - Escalante, Carlos H.; Carmona-Hernández, Fernando A.; Hernández-López, Alberto; Martínez-Mora, Eder I.; Delgado, Francisco; Tamariz, Joaquín
Abstract : A cascade reaction of 2-formyl- N -propargylpyrroles or N -allenyl-2-formylpyrroles with active methylene compounds and ammonium acetate provides indolizines and pyrrolo[1, 2- a ]pyrazines, respectively. Abstract : A straightforward synthesis of indolizines and pyrrolo[1, 2- a ]pyrazines was performed through a cascade condensation/cyclization/aromatization reaction of substituted 2-formyl- N -propargylpyrroles with active methylene compounds such as nitromethane, alkyl malonates, methyl cyanoacetate and malononitrile. Under basic conditions, the reaction proceeded satisfactorily to provide the corresponding 6, 7-disubstituted indolizines. The condensation of the pyrrolic analogues with ammonium acetate gave rise to pyrrolo[1, 2- a ]pyrazines in high yields. N -Allenyl-2-formylpyrroles behaved as more reactive substrates than 2-formyl- N -propargylpyrroles, furnishing the expected indolizines in higher yields. Hence, an allenyl-containing intermediate was probably generated as the reactive species in the reaction mechanism of some N -propargyl pyrroles prior to the cyclization reaction.